Pengaruh Tempat Tumbuh dan Profil Kandungan Kimia Minyak Atsiri dari Rimpang Jahe Merah (Zingiber officinalle Linn. Var rubrum): Influence of Growth Sites and the Chemical Content Profile of Essential Oils from Red Ginger Rhizome (Zingiber officinalle Linn. Var rubrum) - Marwati Marwati; Burhanuddin Taebe; Alfrida Tandilolo; Syamsu Nur (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2021)
Zingiber officinalle Linn. Var rubrum is a typical Indonesian plant that contains lots of essential oils. Essential oils are secondary metabolites of the terpenes which are synthesized through the mevalonic acid pathway. Essential oils in the health sector are used as antiseptic, anti-inflammatory, analgesic and sedative. This study aims to isolation and identification the ratio of the redrhizome ginger essential oil compounds based on the growing location, which were taken from Enrekang and Maros districts.The extraction of essential oils was carried out using the water vapor distillation method, and the essential oils obtained were identified using a GC-MS Spectrophotometer. The results showed that the essential oil of red ginger root from Maros had a yield percentage of 3.8% and 2.7% from Enrekang. Identification of essential oil compounds from the two regions using GC-MC is that eucalyptol, linalyl acetate,1,7,7-trimethylbicyclo[2.2.1]heptan-2-ol, dan citral, eugenol, geranyl acetat, dan citonellol.